Class Discriminaton of Property in Clybourne Park by Bruce Norris - Adene, Yoba; Anwar, Desvalini (English Language and Literature, 2024)
This undergraduate thesis examines the theme of class discrimination in Bruce Norris's play "Clybourne Park" through the theoretical framework of structuralism. By analyzing the structural elements of the play, including language, symbols, and social norms, this study seeks to uncover how class distinctions are portrayed and reinforced within the narrative. Through a close reading of key scenes and characters, the thesis aims to elucidate how structuralism theory can deepen our understanding of the mechanisms by which class discrimination operates in the play.Key words: Clybourne Park, Class discrimination, Property, Structuralism.